Implementasi Metode Diskusi Kelompok Untuk Meningkatkan Hasil Belajar Peserta Didik di SMA PAB 4 Sampali - Ababil, Khairunnisa Mifta (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to investigate the implementation of the group discussion method in improving student learning outcomes at SMA PAB 4 Sampali. The background of this research is based on the low level of active student participation in the learning process, which affects their academic achievement. The group discussion method is considered as one of the learning approaches that can encourage active participation, enhance conceptual understanding, and develop students’ critical thinking skills. This study employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects were subject teachers and students involved in the learning process using the group discussion method. The findings indicate that the implementation of the group discussion method increases students’ activeness in asking questions, expressing opinions, and collaborating, which positively impacts their learning outcomes. Thus, the group discussion method can be considered an effective strategy to improve the quality of learning in schools.